PENGARUH KUALITAS LAYANAN TERHADAP KEUNGGULAN BERSAING DAN KEPUASAN MAHASISWA PADA UNIVERSITAS MUHAMMADIYAH KENDARI - Azis Muthalib, Dzulfikri (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
The title of research is a Effect of service quality on competitive advantage and student satisfaction at the Six Six College of Economics Kendari This study aims to determine and explain the effect of service quality on competitive advantage and student satisfaction at the Kendari Six Six School of Economics. The population in this study were all students at the Six Six Kendari College of Economics. The number of samples in this study were 94 students. This study uses Partial Least Square (PLS) analysis. The results showed that: (1) Service quality had a positive and significant effect on competitive advantage at the Kendari Six Six School of Economics. (2) Service quality has a positive and significant effect on student satisfaction at the Kendari Six Six School of Economics. (3) Competitive advantage has a positive and significant effect on student satisfaction at the Six Six College of Economics Kendari. (4) Competitive advantage can mediate the effect of service quality on student satisfaction at the Kendari Six Six College of Economics.